Le compostage collectif urbain à l'épreuve de ses interdits - Véronique Philippot; Sandrine Glatron (VertigO)
Urban community composting is on the rise in large French cities. In Strasbourg (Alsace), neighborhood or private groups organize composting initiatives, encouraged by local policies and supervised by local authorities. The residents in charge decide and enforce the rules for composting locally. Increasingly, lists of banned inputs are posted, reflecting an effort to control processes in order to avoid inconveniences in shared spaces. While the local authority employees tasked with supervising simply mention ‘undesirable’ inputs as bio-waste material to be monitored, our ethnographic research shows that the risks associated with them are amplified by the residents in charge. The rules are generally easily accepted by accommodating and trusting practitioners, concerned with social cohesion. The prohibited items belong to several categories of biodegradable inputs, often meat products, non-crushed eggshells and citrus, as well as onion, garlic and rotten or moldy leftovers. The arguments put forward to justify these prohibitions draw on various registers ranging from pragmatism (space-time management) to subjective ideology, scientific facts or institutions. However, as the list of banned inputs gets longer, the amount of biomass than can escape incineration diminishes. Encouraging on-site experiments and facilitating access to scientific knowledge about biological processes and the associated organisms might therefore reassure the residents in charge of composting and relax the bans to better respond to the crucial need for reducing waste at the source.